INSTRUMEN PENILAIAN ANGGOTA DPR/DPRD SECARA INDIVIDU DARI PERSPEKTIF KONSTITUEN - WENNY EKA SEPTINA, WENNY EKA SEPTINA (Politika: Jurnal Ilmu Politik, 2014)
Assessment of the performance of members of the DPR/DPRD individually intended to do a wide-breadth, disclosure is related to the extent to which the success or failure of the implementation of the functions of the legislative, especially the delivery of the work to the constituencies that have been selected and given the mandate to occupy a position as a member of the legislature. Assessment of the performance of individual members of the DPR/DPRD can be used as a clear and measurable mechanism to evaluate and improve the quality of the performance of members of the legislative. These instruments can also serve as a benchmark achievement of constituent needs and expectations so that the proper response can be taken against such complaints and demands. Based on the results of research, retrieved 5 (five) of the variables used in the draft performance assessment instruments Member of DPR/DPRD, namely transparency, responsiveness, accountability, credibility, and effectiveness. Five of the above variables was later reduced to several indicators in order for the deployment in the field can be much simpler. The indicators obtained from the aspects contained in the general understanding of related variables used in authors compose this instrument. Keywords: performance assessment instrument, legislative performance individually.